Soluble Epoxide Hydrolase - Sontakke, Pooja M.; Malpani, Suraj G.; Tange, Pooja R.; Ahmad, MD Rayees; Dharashive, Vishweshwar M. (Asian Journal of Pharmaceutical Research and Development, 2024)
Epoxyeicosatrienoic acids (EETs) have numerous cardiovascular benefits, including vasodilation, anti-inflammatory actions, and anti-migratory effects on vascular smooth muscle cells. However, sEH, an enzyme that breaks down EETs into diols, limits these benefits. The development of sEH inhibitors (sEHIs), particularly those based on 1,3-disubstituted urea, has shown promise in enhancing the therapeutic properties of EETs. These inhibitors are antihypertensive and anti-inflammatory and can protect the heart, brain, and kidneys from damage. While there are still challenges to overcome, such as improving the drug-like properties of sEHIs and finding better ways to target specific tissues, the initiation of clinical trials for sEHIs highlights their potential as therapeutic agents.